Odpowiedź :
Odpowiedź:
1. 3x+5= 7
3x= 7-5
3x= 2 /:3
x=2/3
spr.. 3*2/3 +5= 7 ( skracamy 3 i 3 przez 3)
2+5= 7
7=7
L=P
2. -2x-3 = 4
-2x= 4 + 3
-2x= 7 /*(-1)
2x= - 7 /:2
x= - 7/2= - 3 i 1/2
spr... -2 * (-7/2) -3= 4 ( skracamy 2 i 2 przez 2)
-1*(-7) -3= 4
7-3= 4
4=4
L=P
3. -5x+8= - 3
-5x= -3 -8
-5x= - 11 /*(-1)
5x= 11 /:5
x= 11/5 = 2 i 1/5
spr... -5 * 11/5 + 8 = - 3 ( skracamy 5 i 5 przez 5)
-1*11 +8= - 3
-11+8= - 3
-3= - 3
L=P
4. -4x-8 = - 12
-4x = - 12 +8
-4x= -4 /*(-1)
4x=4 /:4
x=1
spr... -4*1 -8= - 12
-4-8= - 12
-12 = - 12
L=P
5. 2x+5= - 10
2x= - 10-5
2x= - 15 /:2
x= - 15/2= - 7 i 1/2
spr... 2*(-15/2) +5= - 10 ( skracamy 2 i 2 przez 2)
-15+5= - 10
-10= - 10
L=P
Szczegółowe wyjaśnienie: